2015
DOI: 10.1118/1.4937933
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous finite element space-angle treatment of the first order linear Boltzmann transport equation with magnetic fields: Application to MRI-guided radiotherapy

Abstract: A discontinuous finite element space-angle approach has been proven to be an accurate method for solving the linear Boltzmann transport equation with magnetic fields for cases relevant to MRI guided radiotherapy. The authors have validated the accuracy of this novel technique against geant4, even in cases of strong magnetic field strengths and low density air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…In the 2015 publication by St-Aubin et al (2015), very accurate results were shown comparing deterministic dose calculations in magnetic fields to Monte Carlo calculations, but it was stated that the iterative solution method used, coupled with the discretization method, produced an unstable iterative scheme in low density media with magnetic fields. In 2016, St-Aubin published a space-angle discontinuous finite element discretization with magnetic fields that was shown to alleviate the iterative instability of the 2015 work (St-Aubin et al 2016). However, a rigorous iterative stability analysis for these novel methods including magnetic fields has not been presented, and is the focus of this work.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2015 publication by St-Aubin et al (2015), very accurate results were shown comparing deterministic dose calculations in magnetic fields to Monte Carlo calculations, but it was stated that the iterative solution method used, coupled with the discretization method, produced an unstable iterative scheme in low density media with magnetic fields. In 2016, St-Aubin published a space-angle discontinuous finite element discretization with magnetic fields that was shown to alleviate the iterative instability of the 2015 work (St-Aubin et al 2016). However, a rigorous iterative stability analysis for these novel methods including magnetic fields has not been presented, and is the focus of this work.…”
Section: Introductionmentioning
confidence: 99%
“…the sign of Ω α •n k will not change for each face over the entire sweep octant). In the previous work (St-Aubin et al 2016) utilizing unstructured tetrahedral spatial meshes, spatial element faces are directed randomly and small angular elements were required to minimize the impact when the sign of Ω α •n k changed over the angular element α. Thus a large number of angular elements were required to span the full unit-sphere leading to an overly complex calculation.…”
Section: Interplay Between Space-angle Discretization Scheme and Spatmentioning
confidence: 99%
“…As such, a key step in the treatment flow is effective planning, where absorbed dose is prescribed to the tumour and upper dose limits are imposed on associated organs at risk (OARs). Dose calculation methods have evolved from correctionbased techniques (Lu 2013, Johns and Cunningham 1983, Papanikolaou et al 2004, Batho 1964, Young and Gaylord 1970 to model-based methods (Karlsson et al 2010, Khan and Gibbons 2014, Mackie et al 1984, Sievinen et al 2005, to state of the art modern methods such as Monte Carlo (Ma et al 2002, Fippel 2013, Gifford et al 2006, St-Aubin et al 2016 and deterministic solvers (St-Aubin et al 2015, Vassiliev et al 2010, Gifford et al 2006. Many modern dose calculation algorithms attempt to solve or approximate the solution of the linear Boltzmann transport equation (LBTE), an integropartial differential equation modelling radiation transport.…”
Section: Introductionmentioning
confidence: 99%
“…the original unmodified weighting function used in the DGFEM, κ is the multigroup magnetic field parameter, given by(Yang et al 2018, St-Aubin et al 2016 …”
mentioning
confidence: 99%